Enantiospecific fate of ibuprofen, ketoprofen and naproxen in a laboratory-scale membrane bioreactor - Hashim, N. H.; Nghiem, L. D.; Stuetz, R. M.; Khan, S. J. (Elsevier, 2011)
The enantiospecific fate of three common pharmaceuticals was monitored in a laboratoryscale membrane bioreactor (MBR). The MBR was operated with a hydraulic retention time of 24 h and a mixed liquor suspended solids concentration of 8.6e10 g/L. Standard solutions of ibuprofen, ketoprofen and naproxen were dosed into the synthetic feed of the MBR. Influent and permeate samples were then collected for enantiospecific analysis. The individual (R)- and (S )-enantiomers of the three pharmaceuticals were derivatised using a chiral derivatizing agent to form pairs of diastereomers, which could then be separated and analysed by gas chromatographyetandem mass spectrometry (GCeMS/MS). Accurate quantitation of individual enantiomers was undertaken by an isotope dilution process. By comparing the total concentration (as the sum of the two enantiomers) in the MBR influent and permeate, ibuprofen, ketoprofen and naproxen concentrations were observed to have been reduced as much as 99%, 43% and 68%, respectively. Furthermore, evidence of enantioselective biodegradation was observed for all three pharmaceuticals. (S )-Ibuprofen was shown to be preferentially degraded compared to (R)-ibuprofen with an average decrease in enantiomeric fraction (EF ) from 0.52 to 0.39. In contrast, (R)-ketoprofen was preferentially degraded compared to (S )-ketoprofen with a relatively minor increase in EF from 0.52 to 0.63. The use of a relatively pure enantiomeric solution of (S )-naproxen resulted in a significant change in EF from 0.99 to 0.65. However, this experiment consistently revealed significantly increased concentrations of (R)-naproxen during MBR treatment. It is hypothesised that the source of this (R)-naproxen was the enantiomeric inversion of (S )-naproxen. Such enantiomeric inversion of chiral pharmaceuticals during wastewater treatment processes has not previously been reported.